Are Plasma Oxytocin and Vasopressin Levels Reflective of Amygdala Activation during the Processing of Negative Emotions? A Preliminary Study - Motoki, Kosuke; Sugiura, Motoaki; Takeuchi, Hikaru; Kotozaki, Yuka; Nakagawa, Seishu; Yokoyama, Ryoichi; Kawashima, Ryuta (Frontiers in Psychology, 2016)
Plasma oxytocin (OT) and arginine vasopressin (AVP) are associated with individual differences in emotional responses and behaviors. The amygdala is considered to be an important brain region for regulating emotion-based behavior, with OT and AVP modulating activity in the amygdala during the processing of negative emotions. In particular, increased OT levels may diminish amygdala activation (anxiolytic effects) and enhanced AVP levels may augment amygdala activation (anxiogenic effects) when negative emotions are processed. A growing body of research has shown that the effects of OT and AVP are modulated by sex: the aforementioned anxiolytic effects of OT and the anxiogenic effects of AVP occur in men, but not in women. However, we have little knowledge regarding the biological mechanisms underlying OT and AVP plasma levels or their respective anxiogenic and anxiolytic effects; similarly, little is known about the causes and nature of sex differences related to these neuropeptides and their effects on emotional processing. In the current study, we focused on the neural functions associated with the biological mechanisms underlying such effects. We hypothesized that amygdala activation would correlate with plasma OT (anxiolytic effects) and AVP (anxiogenic effects) levels because the amygdala is thought to affect the coordinated release of these neuropeptides following affective experiences. We further hypothesized that the effects would be modulated by sex. We assessed 51 participants (male and female) using a paradigm involving negative emotion in conjunction with functional magnetic resonance imaging and measurements of plasma OT and AVP levels. We determined that increased plasma AVP levels were positively associated with amygdala activation (anxiogenic effects) in men, but not in women. These findings highlight the potential underlying neural mechanisms of plasma AVP levels in men.